O-012 Demographic and Lesion Characteristics Outperform Degree of Stenosis in Predicting Outcomes Following Stenting for Symptomatic Intracranial Atherosclerosis. (26th July 2014) - Alexander, M; Cooke, D; Meyers, P; Amans, M; Narvid, J; Dowd, C; Halbach, V; Higashida, R; Hetts, S
Abstract : Introduction: Intracranial atherosclerotic disease (ICAD) is often stratified by degree of stenosis. Additional features such as patient demographics and symptom characteristics also affect lesion behavior and response to treatment. This study compares stratification by degree of narrowing to these additional features. Materials and methods: Retrospective analysis was performed on patients at 4 hospitals with ICAD causing stroke or transient ischemic attack (TIA) treated with stents. Patient demographics, lesion features, symptom characteristics, treatment success, and post-treatment outcomes such as technical complication, transient ischemic attack, stroke, or death were noted. Symptom characteristics were divided by aetiology as hypoperfusion, non-hypoperfusion, or indeterminate. Univariate logistic regression was performed for nominal variable types, and decision trees were constructed using recursive partitioning for continuous variables. Results: Chi-square univariate logistic regression analysis demonstrated significant correlation of female gender with stroke at 30 days (x 2 [1, n = 130] = 5.106, p = 0.024). At point of last clinical contact, TIA was associated with an indeterminate symptom aetiology as opposed to identifiable hypoperfusion or non-hypoperfusion aetiology (x2 [1, n = 130] = 5.556, p = 0.018), as was initial presentation with TIA rather than stroke (x 2 [1, n = 130] = 6.458, p = 0.011). When comparing non-hypoperfusion and indeterminate symptom etiologies against clearly identifiable hypoperfusion aetiology, the non-hypoperfusion group was more likely to have a stroke by point of last contact (x 2 [1, n = 130] = 7.664, p = 0.006). Stroke outcome was also associated with lesion stenosis >95% (x 2 [1, n = 130] = 5.709, p = 0.017). Recursive partitioning analysis confirmed the above-described results and identified age >76.6 years as associated with symptomatic technical complications (x 2 [1, n = 130] = 0.047). Conclusion: Degree of atherosclerotic stenosis is commonly used to stratify lesions when assessing suitability for treatment. This study identified stronger prognostic value in lesion features, specifically pathophysiologic features of presenting symptoms, and patient age and sex. Further research is needed to develop more robust models to predict natural history and potential response to endovascular treatment for ICAD. Disclosures: M. Alexander: None. D. Cooke: None. P. Meyers: None. M. Amans: None. J. Narvid: None. C. Dowd: None. V. Halbach: None. R. Higashida: None. S. Hetts: None.